1971
DOI: 10.3109/00365527109179945
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay and Radioimmunoassay of Plasma Gastrin in a Case of Zollinger-Ellison Syndrome

Abstract: Temperley. J . M . & Stagg, B. H . 1971. Bioassay and Radioimmunoassay of Plasma Gastrin in a Case of Zollinger-Ellison Syndrome. Scurid. 5. Gustrocrii.Fasting plasma gastrin levels were measured i n a patient with the Zollinger-Ellison syndrome by both bioassay and radioimmunoassay. The level remained constant follouing total gastrectomy, but fell sharply follo\iing parathyroidectomy. Although the bioassay gave gastrin levels which were consistently 2 t o 3 times higher than those obtained by radioimmunoassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It cannot be denied that other circulating peptides might react in the assay. It is known that our assay system can detect gastrin degradation products (Lewin, Hunziker, Stagg, and Wyllie, 1971) and it has also been found that some biologically active gastrin-like substances present in the plasma are not detected (Temperley and Stagg, 1971). This implies that the radioimmunoassay cannot measure absolute levels of biologically active gastrin in plasma samples.…”
Section: Discussionmentioning
confidence: 95%
“…It cannot be denied that other circulating peptides might react in the assay. It is known that our assay system can detect gastrin degradation products (Lewin, Hunziker, Stagg, and Wyllie, 1971) and it has also been found that some biologically active gastrin-like substances present in the plasma are not detected (Temperley and Stagg, 1971). This implies that the radioimmunoassay cannot measure absolute levels of biologically active gastrin in plasma samples.…”
Section: Discussionmentioning
confidence: 95%
“…The basal acid output of the stomach (BAO) was 17.9 m-equiv/hr and the maximal histamine response (MHR) using 0.04 mg histamine acid phosphate per kg by intravenous infusion was 23-8 m-equiv/hr giving a ratio BAO: MHR of 75%. Results of plasma gastrin assays (resting) were: radioimmunoassay (Temperley and Stagg, 1971) > 1 ng/ml (normal 80-100 pg/ml), bioassay (Smith, Lawrence, Colin-Jones, and Schild, 1970) 100 ng/ml (normal unrecordable).…”
Section: Case Reportmentioning
confidence: 99%
“…Concentrations of gastrin in the six arterial and venous plasma samples were es timated by both bioassay [10] and radioimmunoassay [11]. Because of random vari ation in both of the assays, each sample was assayed 5-9 times according to the fol lowing plan.…”
Section: Assay Methodsmentioning
confidence: 99%